Persepsi Wajib Pajak Mengenai Penggelapan Pajak, Keadilan Sistem Perpajakan Dan Tax Amnesty Pada Kepatuhan Perpajakan - Merkusiwati, Ni Ketut Lely Aryani; Suaryana, I Gusti Ngurah Agung (E-Jurnal Akuntansi; Vol 31 No 12 (2021)DO - 10.24843/EJA.2021.v31.i12.p13, 2021)
Taxes are the main source of state revenue. Individual taxpayers (WP) have a low contribution to tax revenue in Bali Province. Taxpayer data at the North Badung Pratama Tax Service Office (KPP) explains that there is a delay in submitting the annual SPT, although every year it has begun to decrease. This condition indicates a non-compliant attitude of the WP. This study aims to analyze the effect of perceptions of tax evasion, tax justice, Tax Amnesty on tax compliance. The sample in the study was determined by simple random sampling technique. The number of research samples is 100 taxpayers. PLS SEM analysis. The results showed that the higher the perception of tax evasion, the greater the tax non-compliance. The perception of fairness of the taxation system has no effect on tax compliance. The more taxpayers carry out Tax Amnesty, the smaller the initial level of compliance with the tax system. Keywords : Tax evasion; Fairness of the Taxation System; Tax Amnesty; Tax Compliance.